A silicon negative electrode material and its preparation method and application

By covering the surface of the silicon material with carbon material, the problem of high volume expansion rate of silicon material during charging and discharging of lithium-ion batteries is solved, and the electrochemical performance and life of the battery are improved.

CN115172685BActive Publication Date: 2025-04-29DONGFENG MOTOR GRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210737795.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-22
Publication Date
2025-04-29
Estimated Expiration
2042-06-22

AI Technical Summary

Technical Problem

The volume expansion rate of silicon materials during the charging and discharging of lithium-ion batteries is high, resulting in a short battery life.

Method used

Carbon material is used to coat the surface of the silicon material to inhibit the volume expansion of the silicon material during the electrochemical process. The specific method includes mixing the organic material with the silicon material and grinding, drying and carbonizing to form a carbon-coated silicon negative electrode material.

Benefits of technology

By carbon-covering silicon material, the volume expansion of silicon material is effectively suppressed, its electrochemical performance is improved, and the life of lithium-ion batteries is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172685B_ABST
    Figure CN115172685B_ABST
Patent Text Reader

Abstract

The present invention particularly relates to a silicon negative electrode material and a preparation method and application thereof, belonging to the technical field of lithium-ion batteries. The silicon negative electrode material comprises a carbon material and a silicon material. The carbon material is coated on the surface of the silicon material to inhibit the volume expansion of the silicon material during an electrochemical process. The carbon coating on the silicon surface inhibits the volume expansion of the silicon material during an electrochemical process, improves its electrochemical performance, and solves the problem of high volume expansion rate of the current silicon material during charge and discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a silicon negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of large specific capacity and high specific energy density. They can be charged and discharged quickly and have a long service life. They are one of the most promising energy storage devices. As a key component of new energy electric vehicles, the energy density of power batteries determines the vehicle's range and directly affects the driver's operating experience. The performance of electrode materials directly affects the electrochemical properties of lithium-ion batteries. The key technology that restricts the energy density of existing lithium-ion batteries lies in the capacity of the negative electrode material. The traditional graphite negative electrode has limited space to accommodate lithium ions, resulting in limited improvement in the energy density of lithium-ion batteries.

[0003] Silicon material (3579mAh g -1 ) has a higher capacity than graphite materials (120-200 mAh g -1 ), which can effectively improve the energy density of lithium-ion batteries. However, silicon materials have the technical problems of high volume expansion rate during charge and discharge and short battery life. Summary of the invention

[0004] The purpose of the present application is to provide a silicon negative electrode material and a preparation method and application thereof, so as to solve the problem of high volume expansion rate of silicon material during charge and discharge.

[0005] An embodiment of the present invention provides a silicon negative electrode material, which includes a carbon material and a silicon material, wherein the carbon material is coated on the surface of the silicon material to inhibit the volume expansion of the silicon material during an electrochemical process.

[0006] Optionally, the carbon material is obtained by carbonizing an organic material, and the organic material includes polyvinyl alcohol and / or polyurethane.

[0007] Optionally, the mass ratio of the silicon material to the organic material is (7-9):(5-10).

[0008] Optionally, the silicon material includes nano-foamed silicon.

[0009] Based on the same inventive concept, an embodiment of the present invention further provides a method for preparing the silicon negative electrode material as described above, the method comprising:

[0010] Mixing the organic material and the silicon material to obtain a mixed raw material;

[0011] Grinding the mixed raw material to obtain a grind;

[0012] Drying the ground material to obtain a precursor;

[0013] The precursor is carbonized to obtain a silicon negative electrode material.

[0014] Optionally, the grinding is performed by ball milling, and in the ball milling, the mass ratio of grinding balls to the mixed raw materials is (12-18):1.

[0015] Optionally, the ball milling time is 0.2-0.8h.

[0016] Optionally, the precursor has a water content of 2% to 5% by weight.

[0017] Optionally, the drying temperature is 130-155° C., and the drying time is 20-28 hours.

[0018] Optionally, the carbonization temperature is 750-850° C., and the carbonization time is 1.5-2.5 h.

[0019] Optionally, the carbonization atmosphere is an inert gas.

[0020] Based on the same inventive concept, an embodiment of the present invention further provides an electrode slurry, the raw material of the electrode slurry includes the silicon negative electrode material as described above.

[0021] Optionally, the raw materials of the electrode slurry include silicon negative electrode material, acetylene black and sodium alginate.

[0022] Optionally, the mass ratio of the silicon negative electrode material, acetylene black and sodium alginate is (5-7):(1-3):(1-3).

[0023] Based on the same inventive concept, an embodiment of the present invention further provides a negative electrode, which is made from the electrode slurry as described above.

[0024] Based on the same inventive concept, an embodiment of the present invention further provides a lithium battery, wherein the lithium battery includes a negative electrode, and the negative electrode is the negative electrode as described above.

[0025] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0026] In the silicon negative electrode material provided by the embodiment of the present invention, carbon is coated on the silicon surface to inhibit the volume expansion of the silicon material during the electrochemical process, improve its electrochemical performance, and solve the problem of high volume expansion rate of silicon material during charge and discharge.

[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 is a process flow chart provided by an embodiment of the present invention;

[0030] Figure 2 is a SEM image of the silicon negative electrode material provided by an embodiment of the present invention;

[0031] Figure 3 is the XRD diagram of the silicon negative electrode material provided in Examples 1-5 of the present invention;

[0032] Figure 4 The electrochemical performance curves of the negative electrode materials provided in Example 4 of the present invention and Comparative Examples 1-2;

[0033] Figure 5 It is a flow chart of the method provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0035] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0037] The technical solution of the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0038] According to a typical embodiment of the present invention, a silicon negative electrode material is provided, wherein the silicon negative electrode material comprises a carbon material and a silicon material, wherein the carbon material is coated on the surface of the silicon material to inhibit the volume expansion of the silicon material during an electrochemical process.

[0039] By adopting the above design, carbon is coated on the silicon surface to inhibit the volume expansion of silicon material during the electrochemical process, improve its electrochemical performance, and solve the current problem of high volume expansion rate of silicon material during charge and discharge.

[0040] In some embodiments, the carbon material is prepared by carbonizing an organic material, the organic material includes polyvinyl alcohol and / or polyurethane; and the silicon material includes nano-foamed silicon.

[0041] By adopting the above design, carbon materials are obtained by carbonizing organic materials. The carbon element of the material formed by mixing organic materials with silicon materials is evenly distributed and can be easily coated on the silicon surface to inhibit the volume expansion of the silicon material during the electrochemical process.

[0042] In some embodiments, the mass ratio of the silicon material to the organic material is (7-9):(5-10). The mass ratio of the silicon material to the organic material includes but is not limited to 7:5, 7:6, 7:7, 7:8, 7:9, 7:10, 8:5, 8:6, 8:7, 8:9, 8:10, 9:5, 9:6, 9:7, 9:8 and 9:10.

[0043] The mass ratio of silicon material and organic material is controlled to be (7-9):(5-10) in order to reasonably adjust the carbon / silicon ratio of the product. If the mass ratio is too large, the silicon content will be high, the volume expansion rate of the product will be high during the electrochemical reaction, and the battery life will be shortened. If the mass ratio is too small, the carbon content will be high, which will have good encapsulation of the silicon material but will not be conducive to improving the capacity of the material.

[0044] According to another typical embodiment of the present invention, a method for preparing the silicon negative electrode material as described above is provided, the method comprising:

[0045] S1. Mixing the organic material and the silicon material to obtain a mixed raw material;

[0046] In some embodiments, the mass ratio of silicon material to organic material is (7-9):(5-10). The mass ratio of silicon material to organic material includes but is not limited to 7:5, 7:6, 7:7, 7:8, 7:9, 7:10, 8:5, 8:6, 8:7, 8:9, 8:10, 9:5, 9:6, 9:7, 9:8 and 9:10.

[0047] S2. Grinding the mixed raw material to obtain a grind;

[0048] Specifically, in this embodiment, the organic raw material (polyvinyl alcohol and / or polyurethane) and the nano-foamed silicon material are mixed and ball-milled (mass ratio of grinding balls to raw materials is 15:1) for 0.5 h to form a grinding material.

[0049] In some embodiments, the grinding is performed by ball milling, and in the ball milling, the mass ratio of the grinding balls to the mixed raw materials is (12-18):1. The mass ratio of the grinding balls to the mixed raw materials includes but is not limited to 12:1, 13:1, 14:1, 15:1, 16:1, 17:1 and 18:1, etc.

[0050] The mass ratio of the grinding balls to the mixed raw materials is controlled to be (12-18):1 in order to control the mixed particle size of the product. If the mass ratio is too large, the uniformity of the particle size of the mixture will no longer be improved, which will waste production energy. If the mass ratio is too small, the uniformity of the particle size of the mixture will be poor, which is not conducive to the uniform distribution of carbon and silicon in the composite material.

[0051] In some embodiments, the ball milling time is 0.2-0.8 h, and the ball milling time includes but is not limited to 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h and 0.8 h, etc.

[0052] The reason for controlling the ball milling time to 0.2-0.8h is to control the mixed particle size of the product. If the time value is too large, the disadvantage is that the uniformity of the particle size of the mixture is no longer improved, which wastes production energy. If the time value is too small, the disadvantage is that the uniformity of the particle size of the mixture is poor, which is not conducive to the uniform distribution of carbon and silicon in the composite material.

[0053] S3. Drying the milled material to obtain a precursor;

[0054] Specifically, in this embodiment, the ground material is dried in an oven at 130-155° C. for one day and night (24 hours) to obtain a precursor.

[0055] In some embodiments, the precursor has a water content of 2% to 5% by weight.

[0056] In this embodiment, the drying temperature is 130-155°C, and the drying temperature includes but is not limited to 130°C, 135°C, 140°C, 145°C, 150°C and 155°C, etc. The drying time is 20-28h, and the drying time includes but is not limited to 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h and 28h, etc.

[0057] The reason for controlling the drying temperature to 130-155°C and the time to 20-28h is to control the volume shrinkage of the product. If the value is too large, the product volume shrinks greatly, which is not conducive to the infiltration of the electrolyte; if the value is too small, the product volume is too large and the water content is high, which can easily lead to battery failure.

[0058] S4. Carbonizing the precursor to obtain a silicon negative electrode material.

[0059] Specifically, in this embodiment, under nitrogen protection in a tubular furnace, carbonization was performed at 800° C. for 2 h, and after washing with anhydrous alcohol to a pH of 7, drying was performed at 70° C. in a vacuum environment for 10 h to form a silicon negative electrode material.

[0060] In some embodiments, the carbonization temperature is 750-850°C, including but not limited to 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C and 850°C, etc., and the carbonization time is 1.5-2.5h, including but not limited to 1.5h, 2h and 2.5h.

[0061] In some embodiments, the carbonization atmosphere is an inert gas. In this embodiment, the carbonization atmosphere is nitrogen.

[0062] According to another typical embodiment of the present invention, an electrode slurry is provided, wherein the raw material of the electrode slurry includes the silicon negative electrode material as described above.

[0063] In some embodiments, raw materials of the electrode slurry include silicon negative electrode material, acetylene black and sodium alginate.

[0064] Specifically, the mass ratio of silicon negative electrode material, acetylene black and sodium alginate is (5-7):(1-3):(1-3); the mass ratio of silicon negative electrode material, acetylene black and sodium alginate includes but is not limited to: 5:1:1, 6:2 and 2, 7:3:3, etc.

[0065] According to another typical embodiment of the present invention, a negative electrode is provided. The negative electrode is made from the electrode slurry as described above.

[0066] According to another typical embodiment of the present invention, a lithium battery is provided. The lithium battery includes a negative electrode, and the negative electrode is the negative electrode described above.

[0067] The silicon negative electrode material of the present application, its preparation method and application will be described in detail below in combination with embodiments, comparative examples and experimental data.

[0068] Example 1

[0069] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (9:7.5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0070] Example 2

[0071] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (7:7.5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0072] Example 3

[0073] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (8:10) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0074] Example 4

[0075] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (8:7.5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0076] Example 5

[0077] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (8:5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH = 7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0078] Comparative Example 1

[0079] A negative electrode material, which is a pure carbon material.

[0080] Comparative Example 2

[0081] A negative electrode material, which is a pure silicon material.

[0082] Comparative Example 3

[0083] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (10:7.5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0084] Comparative Example 4

[0085] A method for preparing a silicon negative electrode material, the method comprising: mixing an organic raw material (polyvinyl alcohol / polyurethane) and a nano-foamed silicon material in a mass ratio (8:2.5) and ball milling (ball to raw material mass ratio 15:1) for 0.5 hours to form a mixture. The mixture is dried in an oven at 130-155°C for a day and night (24 hours), carbonized at 800°C for 2 hours in a tubular furnace under nitrogen protection, washed with anhydrous alcohol to pH=7, and dried at 70°C in a vacuum environment for 10 hours to form a silicon negative electrode material.

[0086] Attached Figure 2-4 Detailed description:

[0087] like Figure 2 , which is a SEM image of the silicon negative electrode material provided in an embodiment of the present invention. It can be seen from the image that the product morphology is 3-5 μm irregular agglomerates;

[0088] like Figure 3 , which are XRD patterns of silicon negative electrode materials provided in Examples 1-5 of the present invention, indicating that the products at different mass ratios are silicon-amorphous carbon composite materials;

[0089] like Figure 4 As shown in the figure, it is the electrochemical performance curve of the negative electrode material provided by Example 4 of the present invention and Comparative Examples 1-2. It can be seen from the figure that the generated carbon-silicon composite material has a higher capacity (900mAh g) than the pure carbon material. -1 Vs 435mAh g -1 ), has better stability than pure silicon materials. At different rates, it has a charge and discharge Coulomb efficiency of nearly 97.5%.

[0090] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0091] (1) The silicon negative electrode material provided in the embodiment of the present invention is made of carbon material by carbonizing organic material. The carbon element of the material formed by mixing the organic material and the silicon material is evenly distributed and can be easily coated on the silicon surface to inhibit the volume expansion of the silicon material during the electrochemical process, thereby improving its electrochemical performance and solving the problem of high volume expansion rate of silicon material during charge and discharge.

[0092] (2) The method provided in the embodiment of the present invention adopts an organic polymer / nano-silicon composite process to prepare a silicon-carbon composite material. The process flow is simple, the structure and performance of the material can be adjusted by adjusting the ratio of raw materials, and the post-processing is green and pollution-free;

[0093] (3) The silicon negative electrode material provided in the embodiment of the present invention is of great benefit to the manufacturing process and cost of low-cost lithium-ion batteries, and reduces the cost of using supercapacitors in new energy vehicles.

[0094] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0095] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0096] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A silicon negative electrode material, characterized in that: The silicon negative electrode material includes a carbon material and a silicon material, wherein the carbon material is coated on the surface of the silicon material to inhibit the volume expansion of the silicon material during the electrochemical process, the carbon material is prepared by carbonizing an organic material, the organic material is polyvinyl alcohol or polyurethane, the silicon material is nano-foamed silicon, the mass ratio of the silicon material to the organic material is (7-9):(5-10), and the silicon negative electrode material is a silicon-amorphous carbon composite material.

2. A method for preparing a silicon negative electrode material as claimed in claim 1, characterized in that: The method comprises: Mixing the organic material and the silicon material to obtain a mixed raw material; Grinding the mixed raw material to obtain a grind; Drying the ground material to obtain a precursor; The precursor is carbonized to obtain a silicon negative electrode material.

3. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: The grinding is performed by ball milling, in which the mass ratio of grinding balls to the mixed raw materials is (12-18):

1.

4. The method for preparing a silicon negative electrode material according to claim 3, characterized in that: The ball milling time is 0.2-0.8h.

5. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: The weight water content of the precursor is 2%-5%.

6. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: The drying temperature is 130-155° C., and the drying time is 20-28 hours.

7. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: The carbonization temperature is 750-850° C., and the carbonization time is 1.5-2.5 hours.

8. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: The carbonization atmosphere is an inert gas.

9. An electrode slurry, characterized in that: The raw material of the electrode slurry includes the silicon negative electrode material as claimed in claim 1.

10. The electrode slurry according to claim 9, characterized in that: The raw materials of the electrode slurry include silicon negative electrode material, acetylene black and sodium alginate.

11. The electrode slurry according to claim 10, characterized in that: The mass ratio of the silicon negative electrode material, acetylene black and sodium alginate is (5-7):(1-3):(1-3).

12. A negative electrode, characterized in that: The negative electrode is made from the electrode slurry according to any one of claims 9 to 11.

13. A lithium battery, characterized in that: The lithium battery comprises a negative electrode, and the negative electrode is the negative electrode according to claim 12.

Citation Information

Patent Citations

  • Organic matter / silicon composite material, battery negative electrode prepared from organic matter / silicon composite material and preparation method

    CN112382763A

  • Silicon-carbon-based negative electrode material and preparation method thereof

    CN112599778A